2019
DOI: 10.1016/j.gie.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield and miss rate of EndoRings in an organized colorectal cancer screening program: the SMART (Study Methodology for ADR-Related Technology) trial

Abstract: Background and aims. The add-on EndoRings has been claimed to improve adenoma detection at colonoscopy, but available data are inconsistent. When testing a new technology, parallel and crossover methodologies measure different outcomes, leaving uncertainty on their correspondence. Aims of this study were to compare the diagnostic yield and miss rate of the EndoRings for colorectal neoplasia.Methods. Consecutive subjects undergoing colonoscopy after a positive fecal immunochemical test (FIT) within organized sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…No studies thus far have looked at the cost associated with AI assistance in colonoscopy screening, and predicted costs for AI products currently in development have not yet been announced or determined. It is worth noting that for other recent technologies shown to improve ADR, including the distal scope tip attachments Endocuff and EndoRings, adoption has been slower than might have been suspected [17,18]. While the specific effect of the incremental cost of these devices on the ▶ pattern of clinical adoption has not been evaluated, such devices provide a helpful reference point for expectations surrounding adoption of CADe technology.…”
Section: Discussionmentioning
confidence: 99%
“…No studies thus far have looked at the cost associated with AI assistance in colonoscopy screening, and predicted costs for AI products currently in development have not yet been announced or determined. It is worth noting that for other recent technologies shown to improve ADR, including the distal scope tip attachments Endocuff and EndoRings, adoption has been slower than might have been suspected [17,18]. While the specific effect of the incremental cost of these devices on the ▶ pattern of clinical adoption has not been evaluated, such devices provide a helpful reference point for expectations surrounding adoption of CADe technology.…”
Section: Discussionmentioning
confidence: 99%
“…25 It has recently been proposed that a clinically relevant correlation between adenoma miss and detection rates might provide further insights on how technology improves colonoscopy outcomes. 26 Unfortunately, lack of relevant studies reporting on adenoma miss rates precluded its inclusion among the endpoints in this meta-analysis. Our analysis showed that ADR was significantly higher with HD-WLE, and no improvement in MAC was evident.…”
Section: Discussionmentioning
confidence: 99%
“…When restricting the analysis to EAC studies[18,32], Endocuff use significantly decreased AMR compared to CC (RR = 0.23, 95%CI: 0.14-0.39). ADR and AMR being in the same outcome direction -both in favor of devise use- has been recently proposed to enhance the validity of the results regarding ADR[33].…”
Section: Discussionmentioning
confidence: 99%